Managing Media and Digital Organizations - Noam, Eli M. author. aut Link
XX, 687 p. 111 illus., 45 illus. in color.
Keywords: What does it take for success in the media business? Creativity, innovation, and performance, of course. Plus experience and good judgment. However, it also requires an understanding of the principles and tools of management. This book summarizes the major dimensions of a business school curriculum and applies them to the entire media, media-tech, and digital sectors. Its chapters cover—in a jargonless, non-technical way—the major management functions. First, creating a media product: the financing of projects and the management of technology, HR, production operations, intellectual assets, and government relations. Second, harvesting the product created: market research, marketing, pricing, and distribution. And third, is the control loop: media accounting and strategy planning. The book’s interdisciplinary approach goes beyond an industry-by-industry coverage and centers around management functions. In the process, this book becomes an indispensable resource for those aiming for a career in the media and digital field, both in startups and established organizations. It is also a work that helps advance the entire field—the management of information resources and products—to a more central role in business analysis. This book is designed to help those already in the sector or those joining it to become creative managers and managerial creatives. It aims to make managers in this field more knowledgeable, less blinded by hype, more effective, more productive, and more responsible. .